Peran Praktek Manajemen Sumber Daya Manusia Dan Pelatihan Kerja Terhadap Kinerja Karyawan Di Toko Dhelitha Gordyn - Siswoyo, Slamet Tedy; Nusantoro, Jawoto; Elsananda, Dhea Alvira (Universitas Muhammadiyah Metro, 2023)
A decrease in the number of buyers causes a decrease in the value of the business. Not only that,there are some employees who tend to be very friendly, not customer oriented and someemployees still have poor performance. Not only selling in the offline market, Dhelitha Gordynalso ventured into online sales, so this study aims to identify HRM practices and work learningon employee performance, either partially or simultaneously. The research design in this study isquantitative, with 30 employees. The sampling method used a special sampling method. Whilethe research phase uses a questionnaire that is distributed to all employees who work at theDhelita Gordin store. The analytical tools used are validity, reliability, normality, linearity, andmultiple regression tests with partial t test decisions, simultaneous f, and coefficient ofdetermination. The results of the survey that some management practices and job training at apoint and at the same time if done correctly, then every employee will gradually begin tounderstand the job and its functions that can improve employee performance.